PENGARUH PERAN TEKNOLOGI, ORIENTASI PASAR, PELATIHAN, DAN INFRASTRUKTUR TERHADAP KEUNGGULAN BERSAING BANK SYARIAH - Himyar Pasrizal (IAIN Batusangkar, 2019)
Management of the organizational environment becomes an important part for a companyin addition to human resource management in order to create competitive advantage. A company mustbe careful in managing its environment both internal and external environment. Internal environmentalfactors such as the ability of human resources, financial capabilities, the role of technology, and marketorientation. While some of the company's external environmental factors include infrastructure supportand training. Changes in the environment are adapted by companies by formulating corporate strategiesand creating competitive advantage. Therefore, Islamic banks in the face of competition from financialinstitutions, especially with conventional banks, must be able to manage the environment professionally.Management of the technological environment, market orientation, and professional training atIslamic banks will be able to increase the competitive advantage of Islamic banks themselves. While themanagement of infrastructure is not a special concern for Islamic banks because it does not have animpact on competitive advantage.